2010
DOI: 10.1177/0363546510376737
|View full text |Cite
|
Sign up to set email alerts
|

High School Concussions in the 2008-2009 Academic Year

Abstract: Background An estimated 136 000 concussions occur per academic year in high schools alone. The effects of repetitive concussions and the potential for catastrophic injury have made concussion an injury of significant concern for young athletes. Purpose The objective of this study was to describe the mechanism of injury, symptoms, and management of sport-related concussions using the High School Reporting Information Online (HS RIO) surveillance system. Study Design Descriptive epidemiology study. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
210
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(219 citation statements)
references
References 28 publications
6
210
0
3
Order By: Relevance
“…This time period was chosen because symptoms resolve within 1 month in 70% to 90% of youth with SRRCs. 6,[16][17][18][19] We conducted a sensitivity analysis using alternate exclusion periods of 2 weeks and 3 months to determine how different time periods affected the estimate. We used 2 weeks as the shortest period based on typical symptom resolution.…”
Section: Figurementioning
confidence: 99%
“…This time period was chosen because symptoms resolve within 1 month in 70% to 90% of youth with SRRCs. 6,[16][17][18][19] We conducted a sensitivity analysis using alternate exclusion periods of 2 weeks and 3 months to determine how different time periods affected the estimate. We used 2 weeks as the shortest period based on typical symptom resolution.…”
Section: Figurementioning
confidence: 99%
“…Mild traumatic brain injury (mTBI) remains one of the most common reasons children present for medical care in the United States, [1][2][3] and concerns about its effects on the developing brain have led to a large number of recent studies examining pediatric concussion. Despite this, the expected course of individual postconcussive symptoms in children has not been well described.…”
mentioning
confidence: 99%
“…Defining the pathophysiology of pediatric SRC is paramount, given the high incidence of this injury, [1][2][3][4][5][6]40 considerable recent lay press attention, and the potential for short-and long-term impact on health and well-being. 13,16,[41][42][43][44][45][46][47] To study similarities and differences between pediatric and adult SRC, we evaluated a small cohort of children with SRC and healthy controls, using ImPACT neurocognitive testing and MRI measures of brain structure, metabolism, organization, and blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…If a concussed child returns too quickly to strenuous physical activity or experiences a second SRC, symptoms and neuropsychological testing deficits frequently worsen. 3,6,14,30,40,96 Investigators have demonstrated measurable biological indicators of this vulnerability in animals 97,98 and human adults. 27 Furthermore, catastrophic outcomes such as the second impact syndrome (death resulting after a second concussive type injury) have been attributed to probable loss of cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%